SOME REMARKS ON DUALITY AND OPTIMALITY OF A CLASS OF CONSTRAINED CONVEX QUADRATIC MINIMIZATION PROBLEMS - ROY, Sudipta; CHATTERJEE, Sandip; MUKHERJEE, R. N. (Yugoslav Journal of Operations Research; Vol 27 No 2 (2017), 2017)
In this paper, the duality and optimality of a class of constrained convex quadratic optimization problems have been studied. Furthermore, the global optimality condition of a class of interval quadratic minimization problems has also been discussed. Keywords: Quadratic Forms, Semidenite Matrices, Lagrangian Duality.